The 8 steps to strategic success : unleashing the power of engagement - Van Den Berg, Gerben; Pietersma, Paul (London, United Kingdom : Kogan Page Limited, 2014)
The 8 steps to strategic success brings together the most well-known and most powerful strategy models, from Porter's 5 forces to the balanced scorecard. With this book you will discover how to unleash the power of engagement to design an effective, 21st-century strategy process for your organization.
Engagement on strategic level -- The 8 steps to strategic success revealed -- Key strategy models -- Key engagement methods -- Applying the strategic dialogue
Includes bibliographical references and index.
Keywords: STRATEGIC PLANNING